Prevalence and Associations of Hypertension in Sri Lankan Adults: Estimates from the SLHAS 2018-19 Survey Using JNC7 and ACC/AHA 2017 Guidelines - Ravindra P. Rannan-Eliya; Nilmini Wijemunige; Prasadini Perera; Yasodhara Kapuge; Nishani Gunawardana; Chathurani Sigera; H. M. M. Herath; Bilesha Perera; Anuji Gamage; Nethmi Weerawardena; Ishwari Sivagnanam; SLHAS Collaborators (Ubiquity Press, 2022)
Background: Sri Lanka lacks robust estimates of hypertension (HTN) prevalence owing to few national studies, hindering optimization of control strategies. Evidence on how the revised 2017 American College of Cardiology/American Heart Association (ACC/AHA) HTN definition affects prevalence in low- and middle-income countries (LMICs) is also limited. Objectives: To make robust estimates of HTN prevalence in the Sri Lankan adult population, and to assess impact of the ACC/AHA 2017 definitions. Methods: Data were sourced from the 2018-2019 first wave of the Sri Lanka Health and Ageing Study (SLHAS), a nationally representative longitudinal study of the noninstitutionalized adult population. After excluding those with missing data and aged <18 years, 6,342 participants (95.1%) were included in the analysis. HTN was defined using either the traditional threshold of systolic BP (SBP) ≥140 mmHg or a diastolic BP (DBP) ≥90 mmHg, or the ACC/AHA 2017 threshold of SBP ≥130 mmHg or DBP ≥80 mmHg, or if taking antihypertensive medication. Results: Estimated prevalence of HTN in all Sri Lankan adults was 28.2% using the traditional definition, and it doubled to 51.3% when applying the ACC/AHA 2017 definition. Of those classified as hypertensive according to the older and ACC/AHA 2017 definitions, 53.4% and 31.2%, respectively, were previously diagnosed. Of the 23.2% of adults reclassified as hypertensive by the ACC/AHA 2017 definition, 16.6% had a history of CVD or diabetes. Increased prevalence was associated with urban residence, socioeconomic status, obesity, and Muslim ethnicity. Prevalence increased with age, but the increase was steeper in women from their 30s. Conclusions: Nearly one in three adult Sri Lankans are hypertensive, requiring antihypertensive treatment. Applying the ACC/AHA 2017 definitions almost doubles numbers, but many of those reclassified would require treatment under recent WHO guidelines. Study findings also suggest that design effects in HTN surveys may be higher than usually assumed.